Menguji Batas Keadilan: Analisis Poligami dalam Perspektif Q.S. An-Nisa Ayat 3 Dan 129 - Rifai, Mirwan Sudarmawan; Basri, Halimah; Miswar, Andi (Media Hukum Indonesia (MHI), 2026)
This study examines the practice of polygamy from the perspective of Qur’an Surah An-Nisā’ verse 3, with particular attention to legal aspects and human rights related to its implementation. Polygamy, defined as a man’s marriage to more than one woman, is explicitly regulated in this verse with justice as its primary condition. Allah SWT sets a maximum limit of four wives, but only for those who are truly able to uphold justice among them. This study focuses on analyzing the meanings of key terms in the verse as well as understanding the concept of physical justice—such as the fulfillment of financial support, division of time, and responsibilities—and emotional justice related to feelings and affection. Although achieving perfect justice in emotional aspects is difficult, Islam emphasizes the obligation to be just in matters that can be practically regulated. Therefore, this research highlights that polygamy as mentioned in Qur’an Surah An-Nisā’ verse 3 is not merely a legal issue, but also a manifestation of moral responsibility and respect for the rights of wives. This approach is expected to provide a more equitable understanding of polygamy based on the principles of social justice and Islamic law.